Tourism, migration, and digital nomadism. A conceptual approach to new global mobilities - Zepeda, Sandra (Anais Brasileiros de Estudos Turísticos, 2025)
Recent research on voluntary international migration movements motivated by lifestyle changes indicates a progressive increase in migration from countries in the North to the Global South (Huete and Mantecón, 2017; Salvà, 2011; Di Campli, 2019; Noorlos, 2013; Tang and Zolkinov, 2021; Hayes, 2014). In the context of new forms of human mobility worldwide, some influenced by economic and demographic factors, new mobility modalities emerge as an emerging paradigm in the social sciences (Sheller and Urry, 2006; Sheller, 2014). The present theoretical-conceptual text aims to study the characteristics, properties and implications of Residential Tourism, International Retirement Migration and Digital Nomadism as analytical categories within this developing conceptual framework. A bibliographic review was carried out in secondary sources, particularly scientific journals, classifying the texts according to their focus and year of publication. The study reveals significant differences in the consumer relationships of residential tourism and International Retirement Migration in perspective with traditional tourism, as well as a greater need to characterize the digital nomad, seen as a hybrid that transits between tourism and residence, modifying its consumption patterns in host destinations and with a high social and cultural cost.